Theme of Tearfulness Phenomenon in the Poetry of Sulaiman bin Sulaiman Al-Nabhan - Al-Muhaili, Marwai Bin Ibrahim Bin Musa (Arts for Linguistic & Literary Studies, 2023)
This study aims to investigate the phenomenon of weeping and tears in the poetry of Sulaiman bin Sulaiman Al-Nabhan. A stylistic approach was adopted to study this phenomenon and highlight its aesthetic and artistic dimensions. The study is organized into an introduction and five sections. The first section dealt with tears over ruins, while the second section focused on tears of separation. The third section examined tears of longing, and the fourth section looked at tears of regret. The fifth section discussed tears of mourning. The study revealed that tears were manifested and utilized in Al-Nabahani poetry in various forms, and that such utilization was attributed to several personal factors, echoing the poet’s persona and articulating his sad emotions in vividly expressed verse.